Insights from Spanish Language and Linguistics Students on Theory-Practice Balance in Teacher Education - Lucas-Oliva, Inés; Moreno-Medina, Irene (Revista Fuentes, 2024)
This study aims to explore the expectations and desires of students pursuing Education Sciences degrees regarding their studies. To meet this objective, and employing a mixed-methods approach with content analysis, the study examined the perspectives of a sample of 423 students enrolled in Primary Education, Early Childhood Education, and Pedagogy programs. Findings reveal a discrepancy between students’ anticipated outcomes and the reality of their university education. While students expect primarily theoretical knowledge from their studies, they express a desire for more practical and professionally oriented training. In conclusion, these insights underscore the need for enhancements in teacher training programs to bridge the gap between academic learning and professional-world pedagogical demands. Addressing these gaps holds the potential to shape a more equitable and sustainable educational landscape for the future, fostering a student body that is more motivated and equipped with the required teaching competence. Further implications of this study are also discussed.